Level of Physical Activity and its Correlation with Mental Health in Community-dwelling Older Individuals: A Cross-sectional Study - Vipra Paragkumar Dalal; Subhash Khatri (Journal of Clinical and Diagnostic Research)
Introduction: The global population is ageing rapidly. Physical activity is one of the important factors that can positively impact physical function, mental health and quality of life. Hence, the promotion of healthy living and active ageing is essential for achieving an active and healthy life during this phase. Aim: To evaluate the level of physical activity and its correlation with mental health in community-dwelling older individuals. Materials and Methods: A cross-sectional study was conducted from November 2023 to January 2024 at the Apollo Institute of Physiotherapy in Ahmedabad, Gujarat, India. Data was collected from various community-dwelling older individuals in East Ahmedabad, Gujarat, India. The nature and purpose of the study were explained and written informed consent was obtained from a total of 111 participants. The level of physical activity was measured using the Rapid Assessment of Physical Activity (RAPA) (in both English and Gujarati versions). Wellbeing status was measured using the World Health Organisation-5 (WHO-5) wellbeing index (also in English and Gujarati versions). Spearman’s correlation coefficient was used to determine the correlation between the level of physical activity and wellbeing status in community-dwelling older individuals. The level of significance was set at a p-value of <0.05. Results: The ages of participants ranged from 60 to 80 years, with a mean age of 70.11±3.98 years. Out of 111 participants, 65 were male (58.56%) and 46 were female (41.44%). The mean RAPA score for the study participants was 2.42±1.14, and the mean WHO-5 wellbeing index score of participants was 13.99±3.39. A positive correlation was found between the level of physical activity and wellbeing status (r-value=0.922, p-value=0.001), which was statistically significant. Conclusion: The present study showed a significant very strong positive correlation between the level of physical activity and the mental health of community-dwelling older individuals. Clinicians may advise older individuals to engage in physical activity to improve their mental health outcomes.